Accompagner la mastérisation de la formation des enseignants en France : un dispositif de régulation pour les formateurs des IUFM - Vincent Grosstephan (Université de Provence, 2015)
This article reports on a study of the consequences of the implementation of a Master Program in Teacher Training on the real work of the teacher trainers from a IUFM (Teacher Training Center). The study first aims at making a diagnosis in order to develop an ongoing training plan/program. It also attempts to highlight how the teachers from this IUFM view and deal with the consequences of the reform in their proper teaching style, on the basis of the analysis of work situations following a methodology adapted from professional teaching practice (Mayen, Métral & Tourmen, 2010) as well as reading tables/grids used to analyze professionals' activity in the Clinic of Activity approach (Clot, 2008). The purpose of this study is also to create appropriate conditions to enable teacher trainers to reclaim their own profession, individually and collectively.